2012
DOI: 10.1002/emmm.201201650
|View full text |Cite
|
Sign up to set email alerts
|

Defining critical roles for NF‐κB p65 and type I interferon in innate immunity to rhinovirus

Abstract: The importance of NF-κB activation and deficient anti-viral interferon induction in the pathogenesis of rhinovirus-induced asthma exacerbations is poorly understood. We provide the first in vivo evidence in man and mouse that rhinovirus infection enhanced bronchial epithelial cell NF-κB p65 nuclear expression, NF-κB p65 DNA binding in lung tissue and NF-κB-regulated airway inflammation. In vitro inhibition of NF-κB reduced rhinovirus-induced pro-inflammatory cytokines but did not affect type I/III interferon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 64 publications
6
97
0
Order By: Relevance
“…Interestingly, we observed an increased expression of RV1B-induced IP-10 by azithromycin. In contrast to pro-inflammatory cytokines, which are under the control of the transcription factor NF-κB (nuclear factor, κ-light chain enhancer of activated B-cells) [34], the transcription of the IP-10 gene is dependent on NF-κB and the IFNs pathway by means of IFN-regulatory factors [16,35,36]. These results are in line with our observation of increased expression of RV1B-induced IFNs by azithromycin treatment in the CF cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we observed an increased expression of RV1B-induced IP-10 by azithromycin. In contrast to pro-inflammatory cytokines, which are under the control of the transcription factor NF-κB (nuclear factor, κ-light chain enhancer of activated B-cells) [34], the transcription of the IP-10 gene is dependent on NF-κB and the IFNs pathway by means of IFN-regulatory factors [16,35,36]. These results are in line with our observation of increased expression of RV1B-induced IFNs by azithromycin treatment in the CF cells.…”
Section: Discussionsupporting
confidence: 90%
“…In vitro and in vivo, type I IFN is important in the host defence against RV, with pre-treatment of endogenous IFN robustly reducing virus load in in vitro cell culture models [15][16][17]. This highlights the potential importance of IFNs as therapies to control RV replication in the human airways and highlights the potential of IFN inducers such as azithromycin as treatments for virus-associated CF exacerbations.…”
Section: Introductionmentioning
confidence: 95%
“…While there is some controversy over whether or not NF‐ κ B p65 is required for RV‐induced IFN transcription (Bartlett et al. 2012), it is possible that CHF6001 and roflumilast are suppressing both IRF3‐ and NF‐ κ B‐mediated gene transcription, as we observed impressive suppression of proinflammatory cytokines and IFNs using either treatment. Studies in other systems have shown that PDE4 inhibitors can inhibit NF‐ κ B p65 activation and NF‐ κ B‐driven inflammatory mediator release (Herve et al.…”
Section: Discussionmentioning
confidence: 72%
“…Pattern recognition receptors (PRRs), such as TLR‐3 in the endosome, and the RIG‐like helicases (RLHs) retinoic acid‐inducible gene‐I and melanoma‐differentiated gene‐5 in the cytoplasm sense viral RNA and elicit a signaling pathway involving activation of the transcription factors IRF3 and NF‐ κ B p65/p50 that lead to IFN and proinflammatory cytokine transcription, respectively (Bartlett et al. 2012; Slater et al. 2010; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation